Crop insurance in India: Key issues and way forward - Ashok Gulati; Prerna Terway; Siraj Hussain (Indian Council for Research on International Economic Relations (ICRIER), 2018)
Farmers in India are exposed to large agriculture risks due to vagaries of nature. One of the most effective mechanisms to mitigate agricultural risks is to have a robust insurance system. Although crop insurance has been in the country since 1972, yet it has been beset with several problems such as lack of transparency, high premium, delay in conducting crop cutting experiments and non-payment/delayed payment of claims to farmers. Realizing the limitations of existing system of crop insurance, a new crop insurance scheme was launched on Baisakhi day, Pradhan Mantri Fasal Bima Yojana (PMFBY), from Kharif 2016. Although the overall area insured has increased by a modest 6.5 percent (from 53.7 million ha in 2015-16 to 57.2 million ha in 2016-17), the number of farmers insured has increased by 20.4 percent (from 47.5 million to 57.2 million), the sum insured has increased by 74 percent (from Rs 115432.4 crore to 200618.9 crore), and premium paid has increased by 298 percent (from Rs 5491.3 crore to Rs 21882 crore) over the same period. The scheme has faced several challenges during its first year of implementation which pertain to extension of cut off dates for registration resulting in high premium rates; delay in submission of yield data to assess damages as the system relies on thousands of Crop Cutting Experiments (CCE); lack of trust in the quality of such data as they are not being video recorded and delay in payment of premium subsidy by the state governments to the insurance companies, etc. The litmus test of any crop insurance program is quick assessment of crop damages and payment of claims into farmers' accounts directly, and from that point of view, the first year of implementation of PMFBY has not been very successful. This paper recommends use of high technology and JAM trinity by linking land records of farmers with their Aadhaar numbers and bank accounts for assessment and faster settlement of claims. A portal linking Core Banking Solution (CBS) and crop insurance is need of the hour giving information on real time basis. India's prowess in Information Technology should come handy to achieve this.
Keywords: Q18; G22; G32; 330; Agricultural Risk; Crop Insurance; India; Premium Subsidy